2016
DOI: 10.3325/cmj.2016.57.194
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy and chronic stress lead toward leptin resistance in the satiety centers and insulin resistance in the hippocampus of Sprague-Dawley rats

Abstract: AimTo evaluate the changes in the expression level of gonadal steroid, insulin, and leptin receptors in the brain of adult Sprague-Dawley female rats due to ovariectomy and/or chronic stress.MethodsSixteen-week-old ovariectomized and non-ovariectomized female Sprague-Dawley rats were divided in two groups and exposed to three 10-day-sessions of sham or chronic stress. After the last stress-session the brains were collected and free-floating immunohistochemical staining was performed using androgen (AR), proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The critical reason for this phenomenon remains unclear given that few studies have assessed the effects of OVX and CMS on the gene expression levels in blood cells, and the available information is currently minimal. However, Ivic et al (2016) recently reported that the expression levels of gonadal steroid receptors, including estrogen receptor-β, were oppositely regulated by OVX and CMS in the hypothalamus. Therefore, it could be hypothesized that estrogen receptor-β expression levels in blood cells may also be oppositely regulated by OVX and CMS, and the opposite regulation of a subset of genes might be elicited.…”
Section: Discussionmentioning
confidence: 99%
“…The critical reason for this phenomenon remains unclear given that few studies have assessed the effects of OVX and CMS on the gene expression levels in blood cells, and the available information is currently minimal. However, Ivic et al (2016) recently reported that the expression levels of gonadal steroid receptors, including estrogen receptor-β, were oppositely regulated by OVX and CMS in the hypothalamus. Therefore, it could be hypothesized that estrogen receptor-β expression levels in blood cells may also be oppositely regulated by OVX and CMS, and the opposite regulation of a subset of genes might be elicited.…”
Section: Discussionmentioning
confidence: 99%
“…The functional mechanism of leptin might be associated with the receptor activator of nuclear factor-κB (RANK)/osteoprotegerin (OPG)/ receptor activator of NF-κB ligand (RANKL) axis. Studies have reported that OPG competitively binds RANK with RANKL to affect osteoclast activity, which is upregulated by leptin, thereby inhibiting the activation and maturation of osteoclasts, reducing bone resorption and bone destruction, and regulating bone metabolism [23,24] . In the present study, the number of osteoclasts was signi cantly reduced after leptin overexpression in Sema4D-overexpressed OVX rats, which further veri ed that the improvement effect of leptin on osteoporosis might be related to the inhibition of osteoclast activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the widely studied hippocampal related neurotrophic activity, several studies have uncovered a central role for hypothalamic neurotrophins, specially BDNF, upon multiple circuits to govern appetite and energy metabolism (Xu et al 2003;Kokoeva 2005b;An et al 2020). Therefore, it is known that behavioral disturbances causing derangement in the HPA axis are, as well, correlated to metabolic outcomes (Ivić et al 2016;Jelenik et al 2018). It was previously shown that chronically stressed rats presented reduced hypothalamic and pituitary VEGF and BDNF mRNA levels (Nowacka et al 2015).…”
Section: Discussionmentioning
confidence: 99%